1999
DOI: 10.1002/(sici)1096-8628(19990806)85:4<419::aid-ajmg21>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular noncompaction and distal chromosome 5q deletion

Abstract: We describe a 7 1/2-year-old girl with mildly unusual phenotype and complex heart disease including ventricular myocardial noncompaction. She was found to have a distal 5q deletion, del(5)(q35.1q35.3). Fluorescent in situ hybridization showed that this deletion included the locus for the cardiac specific homeobox gene, CSX. This suggests that some instances of ventricular myocardial noncompaction may be caused by haploinsufficiency of CSX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 14 publications
3
46
0
1
Order By: Relevance
“…A distal chromosome 5q deletion causes a loss of the cardiac specific gene CSX. This deletion was described in a child with findings of LVNC [Pauli et al 1999].…”
Section: Lim Domain Binding Protein 3 (Zasp/ldp3) and Lamin A/c (Lmna)mentioning
confidence: 89%
“…A distal chromosome 5q deletion causes a loss of the cardiac specific gene CSX. This deletion was described in a child with findings of LVNC [Pauli et al 1999].…”
Section: Lim Domain Binding Protein 3 (Zasp/ldp3) and Lamin A/c (Lmna)mentioning
confidence: 89%
“…These gene products have functions related to cytoskeletal and/or mitochondrial function (Tang et al 2010). Another six loci located on chromosomes 1p36 (Thienpont et al 2007), 1q43 (Kanemoto et al 2006), 5q35 (Pauli et al 1999), 8p23 (Blinder et al 2011), and11p15 (Sasse-Klaassen et al 2004) also have been linked to the phenotype of nonsyndromic LVNC. While a number of genes and candidate loci have been reported with LVNC, only a minority of affecteds have been found to harbor causative mutations (Finsterer et al 2004;Ichida 2009;Tang et al 2010;Xing et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which these mutations produce diverse cardiac malformations remains to be determined. Pauli et al (26) reported a patient with haploinsufficiency of NKX2.5 (CSX) resulting from a distal chromosome 5q deletion that manifested ASD, AV block, and ventricular noncompaction. Because of the large number of our patients who had ASD and AV block, many of the mutations we have identified may function as null alleles.…”
Section: Discussionmentioning
confidence: 99%